PRODUKSI BUDAYA DALAM WEDDING PLANNER PADA MASYARAKAT URBAN - Risky Chairani Putri; Wiwik Sushartami (Universitas Gadjah Mada, 2019)
Wedding has been seen as an example of the reflection of social culture. Changes in wedding culture reflect changes in society. Such a social transformation is reflected in the growing demand for impressive wedding party in the urban areas has made new problems concerning to management and creativity. From the wedding management perspective, this has been caught as opportunities, not only in term of economi gains but also their role in power-knowledge production. In recognition of this non-material aspect of social chenges reflet in wedding party, this research attempts to identify the production of culture wedding planner. This study takes the case of prominent wedding organizer company in Surabaya, Mahar Agung Organizer. The data for this research come form interview with managerial personnel of the the Maha Agung. The result shows that the production of culture in the wedding planner’s activity involves six facets: technology, law and regulation, industry structure, organization structure, occupational career, and market. In addition, the production of culture of wedding planner is not singular, which means it engages the role of client, media, vendor and business competitor. Consequently, the power relation of wedding planner in the production of culture is not dominant. Production of culture of a wedding planner has produced complexity, ambivalence, and contestation which appear through technology, especially the Internet. All of these lead wedding planner to take a creative and ambivalent position, since there is no rule (copyright) in wedding planners industry.